Report of the Study on Agricultural Adjustments in Flood Affected Areas in U.P. - Planning Commission (Planning Commission Government of India, 1972)
The report on Agricultural Adjustments in Flood-Affected Areas of Uttar Pradesh examines strategies to mitigate the impact of chronic flooding on agriculture, particularly in the Khadir lands of the Ganges region. Flood-prone areas, covering approximately 1.77 million hectares annually, experience significant crop, infrastructure, and economic losses, necessitating long-term interventions. Key recommendations include crop diversification during flood-free months, development of efficient irrigation systems through tubewells and pumps, and implementation of pilot projects to test new cropping patterns. Financial and institutional support measures, including subsidies, credit facilities, and machinery hire services, are emphasized to enable adoption by farmers. Additionally, research and development on short-duration, flood-resistant crop varieties and field trials are recommended to enhance productivity. The study underscores that strategic agricultural adjustments combined with institutional backing can stabilize and improve crop yields, providing a model for broader application across flood-affected regions in Uttar Pradesh.
Government of India Planning Commission August 1972
Keywords: Flood-Affected Areas; Uttar Pradesh; Khadir Lands; Agricultural Adjustments; Crop Diversification; Irrigation Development; Pilot Projects; Short-Duration Crops; Flood-Resistant Varieties; Financial Support; Institutional Support; Research and Development